(579) Size of Foreign Loan, Annual Repayment, and Exchange Rate in Programs of Economic Development حجم القرض الخارجي، السداد السنوي، وسعر الصرف في برامج التنمية الاقتصادية - Qayum, A. (معهد التخطيط القومى, 2024)
The study discusses the challenges countries face before deciding to borrow for economic development. The borrowing country must consider the willingness of lending countries to lend and the extent of that willingness. Additionally, it must assess its absorbing capacity, as foreign loans may remain unused if this capacity is not properly evaluated in advance, increasing the economic costs of these loans. Absorbing capacity depends on the availability of managerial, technical, and entrepreneurial skills, as well as the size of the market in some cases. However, the terms of the loans are crucial; loans that lead to a reduction in per capita consumption over a significant part of the repayment period may end up doing more harm than good.